2016
DOI: 10.1038/srep24697
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of aldosterone secretion by Cav1.3

Abstract: Aldosterone-producing adenomas (APAs) vary in phenotype and genotype. Zona glomerulosa (ZG)-like APAs frequently have mutations of an L-type calcium channel (LTCC) CaV1.3. Using a novel antagonist of CaV1.3, compound 8, we investigated the role of CaV1.3 on steroidogenesis in the human adrenocortical cell line, H295R, and in primary human adrenal cells. This investigational drug was compared with the common antihypertensive drug nifedipine, which has 4.5-fold selectivity for the vascular LTCC, CaV1.2, over CaV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…MUT could be tested ex vivo (46), with limited informative value beyond our studies in H295R cells. The most promising path forward, however, involves clinical trials in humans.…”
Section: Discussionmentioning
confidence: 99%
“…MUT could be tested ex vivo (46), with limited informative value beyond our studies in H295R cells. The most promising path forward, however, involves clinical trials in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Gene targeted NGS analysis of DNA from 99 APCC from the 15 BHA adrenals demonstrated that CACNA1D mutations (58 %) were present at a higher prevalence than past seen in normal adrenals [15]. Interestingly, in vitro adrenal cell-based studies have shown that expression of mutated CAC-NA1D increases aldosterone production and this production could be significantly reduced by the calcium channel blocker, nifedipine [75]. The high prevalence of APCC with CACNA1D mutations suggests that research on the efficacy of calcium channel blockers as an inhibitor of BHA aldosterone overproduction should be further examined.…”
Section: Apcc In Preclinical and Overt Primary Aldosteronismmentioning
confidence: 99%
“…Importantly, a recent study showed that excess aldosterone caused by CACNA1D mutations could be inhibited by calcium channel blockers [27], suggesting that such drugs might be useful for APCC-oriented aldosterone overproduction. The current findings support a contribution of APCC to unilateral CT-negative PA, but an APCC role in the more common bilateral CT-negative PA (IHA) remains to be determined.…”
Section: Apcc To Ct-negative Pa Pathwaymentioning
confidence: 99%